Identification Of Salmonella sp. In Smoked Fish In Jayapura City - Mantayborbir, Vyona; Indrayani, Ervina; Izaac, Fransina Alfonsina; Runtuboi, Dirk Y. P. (Jurnal Media Akuakultur Indonesia, 2025)
The purpose of this study was to assess the microbiological quality of smoked fish at the processing center in Jayapura City, Papua. 100 kilograms of smoked fish were tested, samples were taken from producers, distributors, and retailers at three distribution levels. Microbiological tests included identification of Salmonella sp. bacteria and Total Plate Count (TPS) tests. The results of the study were conducted using ANOVA and DMRT further tests at a significance level of 95%. The average TPS value at all distribution levels ranged between 3.379 and 3.509 log cfu/g, which is still within the safe limit for consumption (p>0.05). Each sample tested did not show any Salmonella sp. contamination. This study shows that smoked fish products in Jayapura City are microbiologically safe, but care during distribution needs to be improved, especially in terms of packaging and cleanliness, so that the product continues to satisfy consumers. Consumers can be more satisfied and shelf life can be extended with better hygiene, packaging, and better distribution chain management. The results of this study provide important insights for producers, consumers, and related parties about the quality of Jayapura smoked fish. This information can be used as a basis for fisheries policy and product quality improvement.